The quantity and quality of α‐gal‐specific antibodies differ in individuals with and without delayed red meat allergy. Issue 2 (15th July 2016) - Kollmann, D.; Nagl, B.; Ebner, C.; Emminger, W.; Wöhrl, S.; Kitzmüller, C.; Vrtala, S.; Mangold, A.; Ankersmit, H.‐J.; Bohle, B.
Abstract: Background: IgG to galactose‐α‐1, 3‐galactose (α‐gal) are highly abundant natural antibodies (Ab) in humans. α‐Gal‐specific IgE Ab cause a special form of meat allergy characterized by severe systemic reactions 3–7 h after consumption of red meat. We investigated 20 patients who experienced such reactions and characterized their α‐gal‐specific IgE and IgG responses in more detail. Methods: α‐Gal‐specific IgE was determined by ImmunoCAP. IgE reactivity to meat extract and bovine gamma globulin (BGG) was assessed by immunoblotting and ELISA, respectively. In some experiments, sera were pre‐incubated with α‐gal or protein G to deplete IgG Ab. α‐Gal‐specific IgG1–4 Ab in individuals with and without meat allergy were assessed by ELISA. Results: In immunoblots, BGG was the most frequently recognized meat protein. Binding of IgE and IgG to BGG was confirmed by ELISA and completely abolished after pre‐incubation with α‐gal. Neither the depletion of autologous α‐gal‐specific IgG Ab nor the addition of α‐gal‐specific IgG Ab from nonallergic individuals changed the IgE recognition of BGG of meat‐allergic patients. Meat‐allergic patients showed significantly higher α‐gal‐specific IgG1 and IgG3 Ab than nonallergic individuals, whereas the latter showed significantly higher levels of α‐gal‐specific IgG4 Ab. Conclusion: Patients with delayed meat allergy display IgE and IgG Ab that selectively recognize the α‐gal epitope on BGG. Their enhanced α‐gal‐specific IgE levels are accompanied by high levels of α‐gal‐specific IgG1 devoid of IgE‐blocking activity. This subclass distribution is atypical for food allergies and distinct from natural α‐gal IgG responses in nonallergic individuals.